A study on the deposit (within the meaning of Art. 177 of the COT), the actual forfeiture (art. 178 of the COT), and the resolutive penalty (the last paragraph of Art. 179 of the COT) - Efe Can Yıldırır (Annales de la Faculté de Droit d’Istanbul)
Acts that parties fulfill or undertake to fulfill in order to prove a contract concluded or to be rid of an undertaken commitment are frequently encountered in both daily and commercial life. When taking this situation into consideration, legislators have considered the importance of these types of centuries-old habits by introducing regulations to the Turkish Code of Obligations (TCO) on earnest money, forfeit money, or withdrawal and termination by paying a penalty and attaching certain legal consequences. This study aims to analyze each of these concepts separately in terms of theory and practice. The first section will analyze earnest money from the point of view of its nature, function, and fate in the event of performance or non-performance of the main performance obligation, as well as the application or non-application of the last paragraph of Article 182 in the TCO concerning the reduction of the contractual penalty. In particular, the first section will discuss the provisions of the German Civil Code concerning deposits and their compatibility with Turkish law. The second and third chapters will examine the concepts and similar functions of forfeit money and withdrawal or termination by paying a penalty from the point of view of their nature, their functions, and their fate in the event of performance or non-performance of the main performance obligation, as well as the application or non-application of the last paragraph of Article 182 in the TCO concerning the reduction of the contractual penalty. In this context, these sections will only analyze Swiss law regarding the examination of these concepts, given the exceptional nature of these provisions.